Fertility of Trichocephalus ovis in sheep body - Z. T. Baysarova (Российский паразитологический журнал, 2016)
Production of Trichocephalus ovis eggs in sheep body is studied. Estimation of egg production is carried out by division of the amount of Trichocephalus eggs released from animals feces within one day into the amount of Trichocephalus detected after sheep slaughtering. The maximum reproductive capacity of females T. ovis develops in spring and summer. In winter (January) T. ovis egg production significantly slows down in comparison with the spring period. Fertility of T. оvis in sheep body was in winter 3140,6±214,8 expl./day, in spring 3978,4±245,7, in summer 4291,4±317,3 and in autumn 5572,3±384,2 expl./day. High T. ovis egg production may cause a wide spread of trichocephalosis in sheep in Chechen Republic.